Extrinsic Protein Tyrosine Phosphatase Non-Receptor 22 Signals Contribute to CD8 T Cell Exhaustion and Promote Persistence of Chronic Lymphocytic Choriomeningitis Virus Infection - Jofra, Tatiana; Galvani, Giuseppe; Kuka, Mirela; Di Fonte, Roberta; Mfarrej, Bechara G.; Iannacone, Matteo; Salek-Ardakani, Shahram; Battaglia, Manuela; Fousteri, Georgia (Frontiers in Immunology, 2017)
A genetic variant of the protein tyrosine phosphatase PTPN22 is associated with a wide range of autoimmune diseases; however, the reasons behind its prevalence in the general population remain not completely understood. Recent evidence highlights an important role of autoimmune susceptibility genetic variants in conferring resistance against certain pathogens. In this study, we examined the role of PTPN22 in persistent infection in mice lacking PTPN22 infected with LCMV Cl13. We found that lack of PTPN22 in mice resulted in viral clearance 30 days after infection, which was reflected in their reduced weight loss and overall improved health. PTPN22-/- mice exhibited enhanced virus-specific CD8 and CD4 T cell numbers and functionality and reduced exhausted phenotype. Moreover, mixed bone marrow chimera studies demonstrated no differences in virus-specific CD8 T cell accumulation and function between the PTPN22+/+ and PTPN22-/- compartments, showing that the effects of PTPN22 on CD8 T cells are T cell-extrinsic. Together, these findings identify a CD8 T cell-extrinsic role for PTPN22 in weakening early CD8 T cell responses to collectively promote persistence of a chronic viral infection.